The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/eji.201141586
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous and extrinsic regulation of thymopoiesis inhuman immune system (HIS) mice

Abstract: PortugalHuman Immune System (HIS) mice represent a novel biotechnology platform to dissect human haematopoiesis and immune responses. However, the limited human T-cell development that is observed in HIS mice restricts its utility for these applications. Here, we address whether reduced thymopoiesis in HIS mice reflects an autonomous defect in T-cell precursors and/or a defect in the murine thymic niche. Human thymocyte precursors seed the mouse thymus and their reciprocal interactions with murine thymic epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…45 In addition, soluble IL-15 heterodimers were reported to support survival and proliferation of immature human thymocyte subsets as well as to accelerate thymopoiesis. 46 Taken together, these findings suggest that increased IL-15 bioavailability results in strong systemic growth and mobilization signals for lymphocytes. Therefore, the ability of IL-15 to form stable soluble heterodimers with sIL-15R␣ that circulate in the bloodstream and are transported to sites away from the production makes IL-15 a hormone-like molecule, capable to act at distance, in addition to the membrane-bound heterodimeric cytokine with locally restricted functions during cell-to-cell interaction.…”
Section: E6mentioning
confidence: 89%
“…45 In addition, soluble IL-15 heterodimers were reported to support survival and proliferation of immature human thymocyte subsets as well as to accelerate thymopoiesis. 46 Taken together, these findings suggest that increased IL-15 bioavailability results in strong systemic growth and mobilization signals for lymphocytes. Therefore, the ability of IL-15 to form stable soluble heterodimers with sIL-15R␣ that circulate in the bloodstream and are transported to sites away from the production makes IL-15 a hormone-like molecule, capable to act at distance, in addition to the membrane-bound heterodimeric cytokine with locally restricted functions during cell-to-cell interaction.…”
Section: E6mentioning
confidence: 89%
“…Some groups reported that the introduction of HLA expression by the murine hosts greatly improved human responses in HIS mice (20)(21)(22)(23). Although murine MHC probably plays a major role in thymic selection of human T cells in the chimeras (20,24), none of the previous studies could exclude the generation of a mouserestricted human T cell response, precluding the use of these chimeras as preclinical models for vaccine design or immune responses to infections. Therefore, we generated murine hosts in which murine MHC molecules were replaced by HLA molecules to ensure strict education of the human thymocytes by HLA molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Spleen cells from immunized mice were incubated for 10 min with Fc block, as described in the previous section. Cells were stained for 10 min at RT in FACS buffer with a mix of three HBV-specific pentamers, HLA-A2-env peptides (peptides 183-191 and 348-357) and HLA-A2-core peptide (peptides [18][19][20][21][22][23][24][25][26][27], all the three pentamers being conjugated with allophycocyanin (ProImmune, Oxford, U.K.). As controls, cells were incubated with hepatitis C virus (HCV)-specific pentamers HLA-A2 NS3 peptide (1073-1081).…”
Section: Flow Cytometric Analysesmentioning
confidence: 99%
“…In contrast, the thymus of HIS mice clearly harbors cortical regions, though incomplete [22], that contain chimera TECs and immature CD38 + human thymocytes. In addition, the HIS thymus has medullary regions that contain murine TECs that co-localize with human CD3 + T cells [19,40,41]. Several studies have shown that thymic development in HIS mice seems to recapitulate, at least phenotypically, the main steps of T cell development found in human thymuses.…”
Section: T Cellsmentioning
confidence: 96%
“…Histological analyses of the chimera thymus have shown correct compartmentalization of both murine thymic epithelial cells (TECs) and human thymocytes; however, the latter are less represented than in human fetal thymus [40]. The rudimentary thymus of non-reconstituted hosts is characterized by a predominance of cortical-like TECs among stromal cells and by the absence of a medullary region.…”
Section: T Cellsmentioning
confidence: 99%